THE STUDY OF THE NATURAL GENE POOL OF THE CAUCASUS’ PEARS IN THE ENVIRONMENTS OF ADYGEA - I. A. Bandurko; Z. Sh. Daguzhieva; E. M. Apukhtina (Труды по прикладной ботанике, генетике и селекции, 2018)
The results of a long-term study of pear accessions collected by VIR’s expeditions in the Caucasus and grown in the collection of Maikop Experiment Station are presented. A significant variety of morphological characteristics including diagnostic ones was identified. Accessions with uncharacteristic for western species traits were selected: deciduous sepals (Pyrus caucasica Fed., P. salicifolia Pall., P. syriaca Boiss.), reduced number of seed cavities (2-4) in the fruit (P. salicifolia, P. syriaca, P. zangezura Maleev). Also identified were specific accessions relatively resistant to fungal diseases (P. zangezura, P. balansae Decne., some forms of P. caucasica and P. salicifolia) possessing frost resistance in the environments of Adygea (P. salicifolia, P. medvedevii Rubtz., P. caucasica), drought resistance (P. caucasica, P. salicifolia, P. syriaca), and high yield (P. caucasica, P. salicifolia, P. balansae, P. zangezura). Some species: P. salicifolia, P. complexa Rubtz., P. medvedevii, P. syriaca, P. elata Rubtz. were selected as promising for landscaping and breeding of ornamental forms.